2010
DOI: 10.1017/s1041610210001572
|View full text |Cite
|
Sign up to set email alerts
|

Is there a familial overlap between dementia and other psychiatric disorders?

Abstract: There is a possible genetic overlap between dementia and psychosis. This appears to be more pronounced with early onset dementia than with late onset dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…To date, only a few studies have addressed the question of familial comorbidity in schizophrenia and dementia, and they have generated opposing findings. Our findings in this study were consistent with the prior findings of no coaggregation between schizophrenia and Alzheimer's dementia from the larger case-control studies [ 11 , 20 ], but they were in discrepancy with the finding of coaggregation between psychosis or mental disorders and Alzheimer's dementia in other case-control studies [ 21 , 23 ]. However, the latter studies were confined by very small sample sizes, making the associations found debatable.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…To date, only a few studies have addressed the question of familial comorbidity in schizophrenia and dementia, and they have generated opposing findings. Our findings in this study were consistent with the prior findings of no coaggregation between schizophrenia and Alzheimer's dementia from the larger case-control studies [ 11 , 20 ], but they were in discrepancy with the finding of coaggregation between psychosis or mental disorders and Alzheimer's dementia in other case-control studies [ 21 , 23 ]. However, the latter studies were confined by very small sample sizes, making the associations found debatable.…”
Section: Discussionsupporting
confidence: 70%
“…To elucidate the relationship between schizophrenia and dementia, other studies have addressed the question of familial coaggregation between the two disorders. These studies have yielded incongruent results, with 2 case-control studies [ 11 , 20 ] finding no co-occurrence of schizophrenia and dementia (except frontotemporal dementia), and 3 case-control studies [ 21 , 22 , 23 ] finding increased incidence of mental disorders and psychoses in first-degree relatives of dementia probands. These studies are characterized by a limited number of cases, missing contemplation of dementia as a heterogeneous syndromic entity, and the use of a case-control design, which may have led to a considerable recall bias regarding psychiatric history, making it difficult to distill the findings and to draw any substantial conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation with the prior study conducted at our institute where the significantly higher morbid risk for psychosis in EOAD proband families was reported using survival analysis, 16 we…”
Section: Discussionmentioning
confidence: 75%
“…In continuation with the prior study conducted at our institute where the significantly higher morbid risk for psychosis in EOAD proband families was reported using survival analysis, 16 we proposed to study the familial loading of dementia in families of patients with schizophrenia to establish the familial coaggregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation